A randomized clinical trial to assess the efficacy of trial-based cognitive therapy compared to prolonged exposure for post-traumatic stress disorder: preliminary findings. (26th August 2021) - Duran, Érica Panzani; Corchs, Felipe; Vianna, Andrea; Araújo, Álvaro Cabral; Del Real, Natália; Silva, Cláudio; Ferreira, Ana Paula; De Vitto Francez, Paula; Godói, Cláudio; Silveira, Helena; Matsumoto, Lina; Gebara, Cristiane Maluhy; et al.
Abstract: Background: Post-traumatic stress disorder (PTSD) is a prevalent mental health condition that is often associated with psychiatric comorbidities and changes in quality of life. Prolonged exposure therapy (PE) is considered the gold standard psychological treatment for PTSD, but treatment resistance and relapse rates are high. Trial-based cognitive therapy (TBCT) is an effective treatment for depression and social anxiety disorder, and its structure seems particularly promising for PTSD. Therefore, we evaluated the efficacy of TBCT compared to PE in patients with PTSD. Methods: Ninety-five patients (77.6% females) who met Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, Text Revision, criteria for PTSD were randomly assigned to receive either TBCT (n = 44) or PE (n = 51). Patients were evaluated before and after treatment, and at follow-up 3 months after treatment. The primary outcome was improvement in PTSD symptoms as assessed by the Davidson Trauma Scale (DTS). Secondary outcomes were depression, anxiety, and dysfunctional attitudes assessed by the Beck Depression/Anxiety Inventories and Dysfunctional Attitudes Scale, as well as the dropout rate. Results: A significant reduction in DTS scores was observed in both arms, but no significant difference between treatments. Regarding the secondary outcomes, we found significant differences in depressive symptoms in favor of TBCT, and the dropout rate was lower in the TBCT group than the PE group. Conclusion: Our preliminary results suggest that TBCT may be an effective alternative for treating PTSD. Further research is needed to better understand its role and the mechanisms of change in the treatment of this disorder.